Social Entrepreneurship and Woman Empowerment Study Exploratory for Poverty Alleviation - Pitaloka, Lola Kurnia; Astuti, Dwi Puji; Mudrikah, Saringatun; Alfianti, Ririn (Efficient: Indonesian Journal of Development Economics, 2020)
Poverty is still a basic and major problem for all countries, including developing countries. There have been several government efforts undertaken to alleviate poverty but they have not yielded good results. The idea of ​​social entrepreneurship has been widely applied by many countries in an effort to reduce poverty. Empowering women is one way to reduce the high unemployment rate because most of the unemployed are women. The purpose of this study was to see the effect of social entrepreneurship and women's empowerment on poverty alleviation. The research was conducted in Kajeksan Village, Kudus Regency, Central Java with an exploratory quantitative research model where the aim is to explore deeper ideas on how to alleviate poverty through the existing sample. The sample was calculated using the Slovin formula and obtained 145 poor women. The sampling technique used random sampling and data collection using a questionnaire. The data that has been collected will be analyzed using SEM with the help of the WarpPLS analysis tool. The results of this study prove that social entrepreneurship and women's empowerment have a significant effect on poverty alleviation. Kemiskinan masih menjadi masalah dasar dan besar bagi seluruh negara termasuk pada negara berkembang. Telah ada beberapa upaya pemerintah yang dilakukan untuk mengentaskan kemiskinan namun ternyata belum juga memberikan hasil yang baik. Gagasan kewirausahaan sosial telah banyak diterapkan banyak negara sebagai upaya mengurangi penduduk miskin. Memberdayakan perempuan merupakan salah satu cara agar dapat mengurangi tingkat pengangguran yang tinggi karena sebagian besar pengangguran adalah perempuan. Tujuan dari penelitian ini adalah melihat pengaruh kewirausahaan sosial dan pemberdayaan perempuan terhadap pengentasan kemiskinan. Penelitian dilakukan di Desa Kajeksan Kabupaten Kudus, Jawa Tengah dengan model penelitian kuantitatif eksploratori yang mana tujuannya adalah untuk mendalami ide lebih dalam tentang cara mengentaskan kemiskinan melalui sampel yang ada. Sampel dihitung menggunakan rumus slovin dan didapat 145 perempuan penduduk miskin. Teknik pengambilan sampel menggunakan random sampling dan pengambilan data menggunakan kuesioner. Data yang sudah terkumpul akan dianalisis menggunakan SEM dengan bantuan alat analisis WarpPLS. Hasil dari penelitian ini membuktikan bahwa kewirausahaan sosial dan pemberdayaan perempuan berpengaruh signifikan terhadap pengentasan kemiskinan.